HUBUNGAN TINGKAT KECEMASAN DENGAN KUALITAS TIDUR PADA PENDERITA ASMA DI RUMAH SAKIT UMUM KINAPIT KOTA KOTAMOBAGU - Dundo, Lala (Journal Of Community & Emergency, 2024)
Asthma is a chronic non-communicable lung disease, asthma attacks often occur repeatedly and suddenly. According to the Ministry of Health of the Republic of Indonesia, by 2020, asthma sufferers in Indonesia will reach 3.5 million people, the incidence of asthma is estimated to continue to increase by 4 million people every year, there are 250,000 deaths due to asthma. Anxiety is a normal reaction to situations that are very stressful for a person’s life. Anxiety can appear or combine with other symptoms of various emotional disorders. The purpose of the study was to determine the relationship between anxiety and sleep quality in asthmatics at Kinapit General Hospital Kota Kotamobagu. This research is an analytical descriptive type using a cross sectional study that is descriptive analytic in August 2022 and the research location is at the Kinapit General Hospital Kotamobagu. In this study, the sample size was determined by proposive sampling with a total of 32 respondents. The statistical test used is the "Chi-square" statistical test with a 95% confidence degree if . The results showed that the P value = 0.009 while the value of = 0.05 so that the P value = 0.007 < = 0.05. Thus Ho is rejected and H1 is accepted, then there is a significant relationship between Anxiety Levels and Sleep Quality in Asthma Patients at Kinapit Hospital, Kotamobagu City. The conclusion in this study is that the level of anxiety in asthmatics at the Kinapit Hospital in Kotamobagu City is mostly categorized as moderate. The sleep quality of asthmatics at the Kinapit Hospital in Kotamobagu is mostly categorized as poor. Kotamobagu. Suggestions in this study is that this research serves as information for hospital institutions so that health services regarding prevention and treatment of asthma sufferers are caused by various precipitating factors.